2016
DOI: 10.1186/s13148-016-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

In epithelial cancers, aberrant COL17A1 promoter methylation predicts its misexpression and increased invasion

Abstract: BackgroundMetastasis is a leading cause of death among cancer patients. In the tumor microenvironment, altered levels of extracellular matrix proteins, such as collagens, can facilitate the first steps of cancer cell metastasis, including invasion into surrounding tissue and intravasation into the blood stream. However, the degree of misexpression of collagen genes in tumors remains understudied, even though this knowledge could greatly facilitate the development of cancer treatment options aimed at preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 43 publications
1
61
0
2
Order By: Relevance
“…The increased expression of COLIV and COLVI and the collagen structure reflect tumor angiogenesis and glioblastoma progression [162]. Even hypomethylation of the COL17A1 promoter is associated with advanced stage, increased invasion of breast cancer, lung adenocarcinoma, cervical cancer, neck SCC, and lung SCC [163]. Factors other than collagen content are correlated with clinical outcome [164], such as collagen alignment and distribution, which also affect cancer.…”
Section: Collagen and Clinical Applicationsmentioning
confidence: 99%
“…The increased expression of COLIV and COLVI and the collagen structure reflect tumor angiogenesis and glioblastoma progression [162]. Even hypomethylation of the COL17A1 promoter is associated with advanced stage, increased invasion of breast cancer, lung adenocarcinoma, cervical cancer, neck SCC, and lung SCC [163]. Factors other than collagen content are correlated with clinical outcome [164], such as collagen alignment and distribution, which also affect cancer.…”
Section: Collagen and Clinical Applicationsmentioning
confidence: 99%
“…At the transcriptional level, overexpression of collagen XVII mRNA was found in the invasive tumors via reverse-transcriptase polymerase chain reaction (RT-PCR) at the epidermal level and within epithelial tissues. RT-PCR and northern hybridization confirmed the enhanced expression of collagen XVII in SCC (7,55). Among oral keratinocytes stimulated with the tumor promoting phorbol ester (56), a 1.5-fold induction in collagen XVII mRNA expression was noted (53).…”
Section: Squamous Cell Carcinomamentioning
confidence: 70%
“…The mechanism of tumor progression from the perspective of tumor stroma has provided a new outlook on cancer development. Following this model, studies have shown that extracellular matrix (ECM), historically considered a structural barrier to tumor cell migration, likely facilitates the first steps of cancer cell metastasis and supports tumor progression (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…COL17A1 : codifica a cadeia alfa da proteína transmembrana colágeno XVII. No microambiente tumoral, níveis alterados de proteínas de matriz extracelular (como colágeno) podem facilitar os primeiros passos da invasão celular (metástase) em outros tecidos e sangue (Thangavelu et al 2016) . Particularmente, metilações no promotor de COL17A1 foram associadas com pior prognóstico no câncer epitelial (Thangavelu et al 2016) .…”
Section: V7 Genes Diferencialmente Expressos No Pdacunclassified
“…No microambiente tumoral, níveis alterados de proteínas de matriz extracelular (como colágeno) podem facilitar os primeiros passos da invasão celular (metástase) em outros tecidos e sangue (Thangavelu et al 2016) . Particularmente, metilações no promotor de COL17A1 foram associadas com pior prognóstico no câncer epitelial (Thangavelu et al 2016) . A sobre-expressão de UCA1 também foi correlacionada com resistência a quimioterápicos como gemcitabina, cisplatina, tamoxifen, 5-FU, imatinib e EGFR-TKIs, enquanto que a inativação de UCA1 restabelece a sensibilidade às drogas (H. Wang et al 2017) .…”
Section: V7 Genes Diferencialmente Expressos No Pdacunclassified